Intercultural competence development for prospective physical education teachers: Insights from Kazakhstan - Mukhpulova, Rumilyam; Sarsenbayeva, Lyaziza; Urazgaliyeva, Svetlana; Mukhpulova, Rashidam; Bazilgalamova, Assel (Journal of Interdisciplinary Studies in Education, 2025)
This study demonstrates the intercultural communicative competence of future physical education teachers. The role of sports in human culture has been studied, with intercultural communication promoting a humanistic worldview. A critical approach, based on theoretical, empirical, and statistical methods, was employed. The study population comprised third-year students specializing in “physical education and sports” at the Kazakh Academy of Sports and Tourism (n=240). Online surveys were conducted among Kazakh and Russian populations using Google Forms and analyzed using Excel and IBM SPSS Statistics. The levels of students in English (with a professional orientation), cultural intelligence, motivation to teach physical education, emotional intelligence, and tolerance were also studied. The results revealed a positive correlation between almost all the indicators studied. Therefore, a program was developed to improve the intercultural competence of future physical education teachers. The application of the program for one academic year had a positive effect on all the indicators studied, characterizing the overall level of intercultural competence of future physical education teachers.